Риторичний потенціал формування дискурсивного мовлення у майбутніх вихователів закладу дошкільної освіти - Омеляненко, Алла Володимирівна (Полтава, 2022)
Риторичний потенціал автор розглядає як суттєвий компонент формування культури риторичної особистості вихователя, який володіє мистецтвом переконливого мовлення та може навчити цього мистецтва своїх вихованців, студентів
Rhetorical potential of formation of discursive speech in future teachers of preschool education institution
The author considers the rhetorical potential as an essential component of the formation of the culture of the rhetorical personality of an educator who possesses the art of persuasive speech and can teach this art to his pupils, students.